2016
DOI: 10.1038/srep20647
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional associations between rheumatoid arthritis and depression: a nationwide longitudinal study

Abstract: Rheumatoid arthritis (RA) and depression may be associated with each other pathophysiologically, but few studies have been conducted on the interplay between these two diseases using longitudinal measurement. Therefore, we used the National Health Insurance Research Database of Taiwan to investigate the bidirectional associations between RA and depression. One cohort was included to analyze RA predicting the onset of depression and a second cohort for analysis of depression predicting RA. A sex- and age-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 28 publications
6
84
0
2
Order By: Relevance
“…Similar to our study, 2 previous studies in Taiwan reported an increased incidence of depression in the RA population as compared to controls . Although the prevalence of anxiety disorders is reportedly increased in RA , we could not identify prior studies reporting the incidence of anxiety disorders.…”
Section: Discussionsupporting
confidence: 68%
“…Similar to our study, 2 previous studies in Taiwan reported an increased incidence of depression in the RA population as compared to controls . Although the prevalence of anxiety disorders is reportedly increased in RA , we could not identify prior studies reporting the incidence of anxiety disorders.…”
Section: Discussionsupporting
confidence: 68%
“…Chronic pain can independently contribute to the pathogenesis of depression, through elevation of inflammatory cytokines IL‐1β, IL‐6, and TNF‐α . Here, we review the prevalence and characteristics of depression, and its correlation to the levels of inflammatory cytokines and disease activity among different CTD (Tables and ).…”
Section: Depression In Connective Tissue Diseasesmentioning
confidence: 99%
“…As with most complex biologic systems, the relationship between depression and RA is multifactorial with contributory factors involving both the individual characteristics of the patient (including low socioeconomic status; female sex; ethnicity; decreased social support; comorbidities, such as stroke; chronic kidney disease; and cancer) and the biologic state of the disease . The bidirectional association between RA and depression has been implicated, where findings suggests that RA increases the risk of depression, and vice versa …”
Section: Depression In Connective Tissue Diseasesmentioning
confidence: 99%
“…For example, a longitudinal cohort study reported that individuals with depression had 1.3 times [Hazard Ratio (HR) = 1.3, 95%CI: 1.0–1.7] of the risk of developing arthritis as compared to those without depression [160]. Further, a 14-year, population-based cohort study reported significantly higher incidence (HR = 1.65, 95%CI: 1.41–1.77) of RA among individuals with depression as compared to those without depression [161]. …”
Section: Incident Depression and Arthritismentioning
confidence: 99%